The information content of discounts and premiums on closed-end fund shares - Thompson, Rex (Journal of Financial Economics, 1978)
This paper investigates the extent to which discounts and premiums provide information about future expected rates of return on closed-end investment company shares. It is found that discounted fund shares, adjusted for risk, tended to outperform the market in the period 1940 to 1975. Funds selling at a premium appear to have been bad investments over the same time period. On the basis of these results it is argued that the two-parameter capital asset pricing model does not describe the return generating process of closed-end funds. Other potential areas to search for breakdowns in two-parameter pricing are suggested.